Actin Beta-Like 2 as a New Mediator of Proliferation and Migration in Epithelial Ovarian Cancer - Topalov, Nicole Elisabeth; Mayr, Doris; Scherer, Clemens; Chelariu-Raicu, Anca; Beyer, Susanne; Hester, Anna; Kraus, Fabian; Zheng, Mingjun; Kaltofen, Till; Kolben, Thomas; Burges, Alexander; Mahner, Sven; et al. (Frontiers in Oncology, 2021)
The impact of Actin beta-like 2 (ACTBL2), a novel described actin isoform, on epithelial ovarian cancer (EOC) biology has not been investigated so far. In this study, we analyzed the prognostic and functional significance of ACTBL2 and its regulatory element Nuclear factor of activated T-cells 5 (NFAT5). The expression of ACTBL2 and NFAT5 was examined in tissue microarrays of 156 ovarian cancer patients by immunohistochemistry. Aiming to assess the molecular impact of ACTBL2 on cellular characteristics, functional assays were executed in vitro upon siRNA knockdown of ACTBL2 and NFAT5. ACTBL2 expression was identified as an independent negative prognostic factor for overall survival of EOC patients. EOC cell lines showed a significantly increased mRNA and protein level of ACTBL2 compared to the benign control. In vitro analyses upon siRNA knockdown of ACTBL2 displayed a significantly reduced cellular viability, proliferation and migration. siRNA knockdown of NFAT5 proved a significant molecular interplay by inducing a downregulation of ACTBL2 with a thus resulting concordant alteration in cellular functions, predominantly reflected in a decreased migratory potential of EOC cells. Our results provide significant evidence on the negative prognostic impact of ACTBL2 in EOC, suggesting its crucial importance in ovarian carcinogenesis by modulating cellular motility and proliferation.